PELAKSANAAN PROGRAM SANITASI TOTAL BERBASIS MASYARAKAT (STBM) DAN IMPLIKASINYA TERHADAP PERUBAHAN PERILAKU MASYARAKAT DI KABUPATEN LIMA PULUH KOTA - Elian Sitra; Asdi Agustar; Erwin Erwin (JISPO : Jurnal Ilmu Sosial dan Ilmu Politik, 2019)
This event will be based on research of the program of Community Lead Total Sanitation (CLTS) in Lima Puluh Kota District. This study aims to describe the implementation of the program and to know the changes the behavior of the environmental health of the community by the existence of the CLTS program in Lima Puluh Kota District.This study used a survey method, which is primary data sourced from the respondent became the main data to answer problems that questionable on this research. Data collection was done through in-depth interviews and questionnaires on 75 respondents.The results showed that program execution CLTS ranging from planning, implementation, monitoring and evaluation of the involved community. The community was given a major role in this program. The role of the Government in the program only facilitates CLTS ultimately completely turned over to community self-help. The CLTS programs have succeded in changing knowledge and attitudes towards Open Defecation and Hand Wash Use Soap, but has not succeeded in changing the behavior of society as a whole. The implementation are the first and the second pillar, Stop Open Defecation and Hand Wash Use Soap, while pillars 3, 4, 5 have not been implemented yet.